Empowering Youth Through Creative Digital Content Workshops in Marginalized Areas - Seeletse, Solly Matshonisa (Edujavare Publishing, 2025)
This community service initiative aimed to empower marginalized youth by enhancing their digital literacy and creative skills through workshops focused on digital content creation. The primary objective was to equip participants with the technical skills needed to produce digital media while fostering self-expression and social engagement. Using a Participatory Action Research (PAR) approach, the workshops involved hands-on training in video editing, podcasting, and social media management while encouraging collaboration and storytelling on local issues. The results indicated a significant improvement in technical skills and self-confidence among participants, with 85% reporting increased proficiency in content creation tools. Moreover, the workshops promoted a sense of community and empowerment, as youth collaborated on projects addressing social issues and showcased their work in a final exhibition. The findings highlighted the transformative power of creative digital education in marginalized communities, bridging the digital divide and offering youth a platform to assert their identities. Despite challenges such as unequal access to technology and varying initial skill levels, the initiative demonstrated the potential of digital content creation programs to foster empowerment, social cohesion, and critical engagement. The contributions of this initiative are significant in promoting inclusive digital literacy programs and offering a model for future community-driven digital education.